Following the bend : how to read a river and understand its nature - Wohl, Ellen E., 1962- (Princeton University Press, 2025)
"An engaging and thought-provoking introduction to river scienceWhen we look at a river, either up close or while flying over a river valley, what are we really seeing? Following the Bend takes readers on a majestic journey by water to find answers, along the way shedding light on the key concepts of modern river science, from hydrology and water chemistry to stream and wetland ecology.In this accessible and uniquely personal book, Ellen Wohl explains how to "read" a river, blending the latest science with her own personal experiences as a geologist and naturalist who has worked on rivers for more than three decades. She charts how water travels through the hydrologic cycle around the globe and downstream to distribute energy, move sediment, and shape river channels, and how living organisms adapt to life in flowing water to create vibrant river ecosystems. Wohl looks at the role of disturbances such as floods and droughts and discusses how geologists interpret the sedimentary records of past river processes. She illustrates how river networks interact with Earth's surface and considers issues for rivers in the future, such as progressive drying, river restoration, and the legal personhood of a river to maintain its distinctive spirit, identity, and integrity.Sharing a new understanding of how rivers function as both physical systems and ecosystems, Following the Bend enables us to observe rivers with fresh eyes and more fully appreciate the beauty, vibrancy, and complexity our planet's vital waterways"-- Provided by publisher.